N-Terminal Ubiquitination of Amyloidogenic Proteins Triggers Removal of Their Oligomers by the Proteasome Holoenzyme. Issue 2 (17th January 2020) - Ye, Yu; Klenerman, David; Finley, Daniel
Abstract : Aggregation of amyloidogenic proteins is an abnormal biological process implicated in neurodegenerative disorders. Whereas the aggregation process of amyloid-forming proteins has been studied extensively, the mechanism of aggregate removal is poorly understood. We recently demonstrated that proteasomes could fragment filamentous aggregates into smaller entities, restricting aggregate size [1 ]. Here, we show in vitro that UBE2W can modify the N-terminus of both α-synuclein and a tau tetra-repeat domain with a single ubiquitin. We demonstrate that an engineered N-terminal ubiquitin modification changes the aggregation process of both proteins, resulting in the formation of structurally distinct aggregates. Single-molecule approaches further reveal that the proteasome can target soluble oligomers assembled from ubiquitin-modified proteins independently of its peptidase activity, consistent with our recently reported fibril-fragmenting activity. Based on these results, we propose that proteasomes are able to target oligomers assembled from N-terminally ubiquitinated proteins. Our data suggest a possible disassembly mechanism by which N-terminal ubiquitination and the proteasome may together impede aggregate formation. Graphical abstract: Image 1 Highlights: Amyloid proteins α-synuclein and tau K18 can be ubiquitinated by UBE2W. N-terminal ubiquitin modification on amyloid proteins delays aggregation. Proteasomes can remove N-terminal ubiquitin-modified oligomers. Proteasomes remove oligomers primarily by enabling their dissociation.